Elevated Humoral Immune Response to SARS-CoV-2 at High Altitudes Revealed by an Anti-RBD “In-House” ELISA - Tomas-Grau, Rodrigo Hernán; Ploper, Diego; Ávila, César Luis; Vera Pingitore, Esteban; Maldonado Galdeano, Carolina; Chaves, Silvina; Socias, Sergio Benjamín; Stagnetto, Agustín; Navarro, Silvia Adriana; Chahla, Rossana Elena; Aguilar López, Mónica; Llapur, Conrado Juan; et al. (Frontiers in Medicine, 2021)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has caused a global pandemic with dramatic health and socioeconomic consequences. The Coronavirus Disease 2019 (COVID-19) challenges health systems to quickly respond by developing new diagnostic strategies that contribute to identify infected individuals, monitor infections, perform contact-tracing, and limit the spread of the virus. In this brief report, we developed a highly sensitive, specific and precise “In-House” ELISA to correctly discriminate previously SARS-CoV-2-infected and non-infected individuals and study population seroprevalence. Among 758 individuals evaluated for anti-SARS-CoV-2 serology in the province of Tucumán, Argentina, we found a weak correlation between antibodies elicited against the RBD, the receptor-binding domain of the Spike protein, and the nucleocapsid (N) antigens of this virus. Additionally, we detected mild levels of anti-RBD IgG antibodies in 33.6% of individuals diagnosed with COVID-19, while only 19% showed sufficient antibody titers to be considered as plasma donors. No differences in IgG anti-RBD titers were found between women and men, neither in between different age groups ranging from 18 to 60. Surprisingly, individuals from a high altitude village displayed elevated and longer lasting anti-RBD titers compared to those from a lower altitude city. To our knowledge, this is the first report correlating altitude with increased humoral immune response against SARS-CoV-2 infection